Factors Influencing the Rise of House Price in Klang Valley. - Haron, Nuzul Azam; Liew, Cindy (2013)
There is an increase of house price radically in Klang Valley that affect to Malaysian house buyer. House price is the value to be paid for the dealing of buying a residential property. House price rises continuously respecting few factors and had impacting house buyer in decision to buy their house. This study becomes necessary since there is less research that gives information in the factors influencing the rise of house price. The factors are found out through detailed literature reviews and information from pilot study. Pilot study is conducted through interviewing representative from National House Buyer Association, pioneer in solving house related problem, to provide legal suggestion and etc. The data is collected via questionnaire survey form distributed to respondents in sample area. The sample area is Klang Valley region, 10 municipal districts including Kuala Lumpur, the Capital City. In result and analysis stages, the factors had to be refined by analyzing the data using statistical tests. Every single factors are calculated its average index respect to few level of influence under respondents’ opinion. The index will then treated as influencing level of the factors. Based on the study, fluctuation in housing market, increasing in construction cost, population growth and increasing demand are factors which give major influence to rise of house price. The study also identified housing criteria to be considered during setup of house selling price and also preference among house buyer nowadays. This study also identified cost contributors in construction being foresees as control measure concerned in respect to respondents point of view.